Сучасна українська ідентичність як наслідок бездержавного минулого - Скляр, В. (Народна творчість та етнологія, 2015)
У статті розкрито сутність української ідентичності; визначено чинники, які впливали на її формування за часів бездержавності; показано природу російської імперської політики щодо України; встановлено статус українства в Україні за часів бездержавності; окреслено вплив міграційних та асиміляційних процесів на зміни етномовної структури населення України; з’ясовано наслідки інерційного впливу етномовних процесів доби бездержавності на сучасну Україну. В статье раскрыта сущность украинской идентичности; определены факторы, которые влияли на ее формирование во времена безгосударственности; показана природа российской имперской политики относительно Украины; установлен статус украинцев в Украине во времена безгосударственности; определено влияние миграционных и ассимиляционных процессов на изменения этноязыковой структуры населения Украины; раскрыты последствия инерционного воздействия этноязыковых процессов эпохи безгосударственности на современную Украину. Based on the achievements of forerunners, the author reveals the essence of Ukrainian identity. There is also a determination of the factors that have influenced the formation of Ukrainian identity in times of statelessness. Besides that, there is a demonstration of the nature of Russian imperial policy towards Ukraine. There has been ascertained the status of Ukrainianhood in Ukraine during the period of statelessness (a subjugated ethnic majority). There has been outlined the impact of migration and assimilation processes on the changes in the ethnolinguistic structure of the population of Ukraine. And finally, the upshots of the inertial influence of the ethnolinguistic processes in the time of statelessness upon modern-day Ukraine have been ascertained.